1979
DOI: 10.2307/3280332
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Abundance of Enteric Helminths in Chrysemys s. scripta from Various Habitats on the Savannah River Plant in South Carolina

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The American Society of Parasitologists is collaborating with JSTOR to digitize, preserve and extend access to The Journal of Parasitology. ABSTRACT:Nine species of enteric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…Thus, the higher prevalence, abundance and intensity of infection of turtles from Portil may be related to the higher frequency of plant matter in the diet of these turtles than in those from Acebuche (N. Perez-Santigosa, unpublished PhD.). Infection intensities could be also related with the abundance of intermediate hosts in each locality as has been previously described (Esch and Gibbons, 1979a;Esch et al, 1979b).…”
Section: Discussionmentioning
confidence: 85%
“…Thus, the higher prevalence, abundance and intensity of infection of turtles from Portil may be related to the higher frequency of plant matter in the diet of these turtles than in those from Acebuche (N. Perez-Santigosa, unpublished PhD.). Infection intensities could be also related with the abundance of intermediate hosts in each locality as has been previously described (Esch and Gibbons, 1979a;Esch et al, 1979b).…”
Section: Discussionmentioning
confidence: 85%
“…The literature contains numerous studies of parasite population dynamics, most of which address questions of population regulation (e.g., Holmes et aI., 1977;Granath and Esch, 1983;Lemly and Esch, 1984). Others, e.g., Cone and Anderson (1977), Esch et al (1979), Price (1983), and Kennedy et aI. (1986), deal with parasite assemblages as a function of host age, species, or habitat.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the fact that all but one of the parasitized animals were captured in the same area might suggest a stronger relation to dietary habits than to age or sex. According to other authors, T. scripta can accidentally ingest intermediate hosts of trematodes, like snails, when feeding on vegetables (ESCH et al, 1979;KENNEDY et al, 1986). Intensity 1 12 1 11 18 6 33 8 Sex Female Male Female Male Female Female Female Female Table 1: Sex, weight (in grams) and number of trematodes (Intensity) detected on the T. scripta elegans specimens included in this study.…”
mentioning
confidence: 86%
“…In 2008 this number decreased to eight, as a consequence of invasive species control programs (BATALLER et al, 2008). Previous studies reported the presence of nematodes of the genera Falcaustra, Serpinema, Physaloptera, Aplectana and trematodes of the genus Patagium in T. scripta and native turtles in Spain (ESCH et al, 1979;ROCA et al, 2005;HIDALGO-VILA et al, 2006VILLARÁN & DOMÍNGUEZ, 2009;ALARCOS et al, 2010).…”
mentioning
confidence: 94%